Optimal design of membrane processes for wastewater treatment and metal recovery - Corvalán, Sergio (2004)
Different continuous operating modes of a nondispersive solvent extraction (NDSX) process with membrane modules of hollow fibre for wastewater treatment and metal recovery are evaluated. Cocurrent and countercurrent flow of aqueous and organic phases in the membrane modules with alternative product extraction locations for the removal and recovery of hexavalent chromium from wastewater are studied. The design of NDSX process in a countercurrent continuous operation is addressed for the first time in this work and the improvement achieved is reported. The membrane area required in the countercurrent operation is reduced significantly compared with the cocurrent operation, requiring also less investment in pumps and pumping cost leading to the minimum total cost. Thus a significant improvement in the design of this new and cleaner technology is presented.